(untitled) (Revista do Tribunal Regional Federal da 3ª Região, 2021)
Due to the damaging Covid-19 pandemic, we were forced to work electronically. So, in our case, as university professors alone, there were no less than 20 classes, lectures, debates and seminars. And during some of these events, we realized that, in addition to formal doctrinal elements about the 30 years of the CDC, many participants were curious to know behind the scenes of the drafting of this law. So we decided to write something about it, especially in view of our role as vice-president and general rapporteur of the committee that drew up the draft in 1988. In other words: why the definition of consumer also includes legal entities; what is the basis of the so-called qualified product guarantee; what is a collective consumer agreement; what is the reason for the provision for a joint venture between Public Prosecutors’ Offices; why there were some vetoes against the bill approved by Congress, etc. And that’s not to mention the great new features of consumer statute, such as objective civil liability for the fact of the product and service, the possibility of reviewing contractual clauses or even declaring them null and void, a list of abusive practices and clauses, crimes against consumer relations, collective protection in three forms, and so on. On the other hand, it must be said that the CDC was not the first law on the subject. We are not trying to reinvent the wheel. We consulted 14 laws from countries that already had consumer protection laws. We also used the so-called UN Type Law as a basis. Added to these sources of comparative law is the accumulated experience of our jurisprudence and doctrine. We have not set ourselves the task of producing an orthodox piece of doctrine, quite the opposite, but rather to bring to light some clarifications.